Memorial dedicated to Daniel Seton - Ghosh, Ayan (2023)
Memorial dedicated to Daniel Seton, Lieutenant-Governor of Surat Castle, who died on 17th April 1803. In 1612, the East India Company (EIC) had set up their first factory at Surat, which was the seat of the Company’s trade. However, Surat declined in importance when the EIC took possession of Mumbai and made it their focus of commerce and governance.